On One Class of Matrix Topological *-Algebras - Tishchenko, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study a matrix algebra M n(U), where U is a commutative topological nuclear entire (bounded, analytic) *-algebra. We prove that M n(U) is also a topological nuclear entire (bounded, analytic) *-algebra.